Equality in Canada - Nausica Palazzo (Oñati Socio-Legal Series)
This article intends to address the limits associated with a rigid grounds-based approach to equality, requiring claimants to categorize their identity within an enumerated ground to “deserve” the protection of the equality guarantee. To this end, I first shed light on the irreconcilability of rigid grounds with post-structuralist accounts of identity, and then lay claim to an approach to equality that extends its reach to fluid, intersectional groups. Thereafter, taking Canada as a case study, I parse out the Canadian equality jurisprudence, particularly the cases offering an analysis of the aforementioned grounds. I then move to sketch out two proposals to overcome the risks associated with the current equality jurisprudence, by focusing on marital status discrimination. I ultimately offer a cursory overview of the complex interplay between approaches to equality and the organization of interest groups, and illustrate the issues around the organization of “post-identity groups”.